Determination of Lead by the Electrothermal Atomic Absorption Spectrometry in a Candidate Reference Material of Fish Meal Using Chemical Modifiers - Suwari; H. R. Hadiman; Tahid (Journal of Applied Chemical Science, 2012)
Different chemical modifiers for the determination of lead by the electrothermal atomic absorption spectrometry (ETAAS) in a candidate reference material of fish meal matrix were studied. The optimal pyrolysis and atomizing temperatures (TP and TA) of lead obtained by adding modifiers, lanthanum nitrate, magnesium nitrate, and ammonium dihydrogen phosphate ,were (750 and 2300 oC), (600 and 2000 oC) and (650 and 2200 oC), respectively, whereas the TP and TA of the lead without modifier were 450 and 2000 oC, respectively. Performance test of the chemical modifiers are based on dynamic range, characteristic mass, limit of detection, precision, accuracy, sample recovery, and repeatability. The experiment without modifier was carried out as control of the performance. The performance of analytical procedures by adding ammonium dihydrogen phosphate modifier were found that 0.2 - 2.0 ng of the dynamic range, 19 pg of characteristic mass, 16 pg of limit of detection, 3.45 % of precision, 98 ± 3% of sample recovery, and 0.04 ± 0.01 μg/g of repeatability . The application result of the method for the determination of fish meal matrix 0.87 ± 0.03 μg/g of lead. The accuracy of the proposed method was verified by analyzing the certified reference material, cod muscle, BCR CRM 422 and the result was 0.092±0.008 which is almost similar with its certified value, 0.085±0.015. These results indicated that ammonium dihydrogen phosphate is the best choice modifier compared to the other in all aspects cited above.